Textbooks in the EFL classroom: defining, assessing and analyzing - Radić Bojanić, Biljana B.; Topalov, Jagoda P. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The aim of this paper is to define textbooks, analyze their advantages and disadvantages and to explicate the process of textbook selection and reasons for analyzing textbooks. The paper describes two reasons for performing a textbook analysis: evaluating for potential and evaluating for suitability, and further states various processes of textbook content analysis including the analysis of the stated aims and objectives, learner needs, their abilities and preferences, as well as the establishment of criteria in relation to previously set objectives. The paper concludes by stating that the task that teachers are faced with when selecting and evaluating textbooks is not that is an easy one, but it is crucial. With the assistance of clear guidelines and detailed criteria, they should be able to make an informed decision and choose a textbook that is most suitable for the requirements of their specific classroom context.